2019
DOI: 10.1126/sciadv.aax9230
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PTPRE-AS1 modulates M2 macrophage activation and inflammatory diseases by epigenetic promotion of PTPRE

Abstract: PTPRE-AS1 deficiency aggravates pulmonary inflammation but reduces colitis severity by modulating M2 macrophage activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 40 publications
2
79
0
Order By: Relevance
“…The proposed mechanism is that PTPRE-AS1 associates with the chromatin modifying protein WDR5 and guides the deposition of H3K4me3 at the PTPRE promoter. In accordance with this model, reduced levels of PTPRE-AS1 and PTPRE is observed in PBMCs from patients with allergic asthma [79]. Additional lncRNAs, including NIFK-AS1, have been demonstrated to influence M2 polarization of macrophages downstream of IL-4 signaling [80].…”
Section: Lncrna Modes Of Action: Nuclear Activitysupporting
confidence: 64%
See 1 more Smart Citation
“…The proposed mechanism is that PTPRE-AS1 associates with the chromatin modifying protein WDR5 and guides the deposition of H3K4me3 at the PTPRE promoter. In accordance with this model, reduced levels of PTPRE-AS1 and PTPRE is observed in PBMCs from patients with allergic asthma [79]. Additional lncRNAs, including NIFK-AS1, have been demonstrated to influence M2 polarization of macrophages downstream of IL-4 signaling [80].…”
Section: Lncrna Modes Of Action: Nuclear Activitysupporting
confidence: 64%
“…A transcriptome-wide analysis of lncRNAs in bone marrow-derived macrophages (BMDMs) identified the lncRNA PTPRE-AS1 as being significantly induced during the IL-4 mediated maturation of M2 macrophage. [79]. PTPRE-AS1 s genomic position maps to opposite strand of the gene encoding tyrosine phosphatase receptor type E (PTPRE).…”
Section: Lncrna Modes Of Action: Nuclear Activitymentioning
confidence: 99%
“…Researchers have suggested that in ammatory cytokines, especially NF-κΒ play a critical role in regulating lncRNAs in human diseases [9]. miR-489 targeting CHRF in repressing MyD88 and Smad in pulmonary brosis [10], differential expressed NEAT1 correlated with increased in ammation was observed in COPD [11], protein phosphatase ε (PTPRE) was involved in accelerating pulmonary allergic in ammation [12]. Therefore, we hypothesized that speci c lncRNAs might regulate the pathologic processes underlying pulmonary in ammation.…”
Section: Introductionmentioning
confidence: 97%
“…Next, we investigated the role of lnc-BAZ2B and its cis target gene BAZ2B in a mouse model of M2 macrophage-associated, CRE-induced pulmonary inflammation (Fig 5, A). 38 Asthma pathologies developed in CRE-challenged mice, as indicated by the significant recruitment of inflammatory cells to the lung, with dense peribronchial infiltrates and goblet cell hyperplasia in the histologic examination; however, this was not observed in PBS-challenged mice (Fig 5, B). Interestingly, lnc-BAZ2B overexpression in CRE-treated mice significantly enhanced pulmonary inflammation, including increased peribronchial infiltrates and goblet cell hyperplasia, and it increased the total number of infiltrated inflammatory cells, especially eosinophils, in bronchoalveolar lavage fluid and enhanced the expression level of Muc5ac, compared with that in mice treated with CRE only (Fig 5, B-E).…”
Section: Lnc-baz2b and Baz2b Exacerbate Cre-induced Lung Inflammationmentioning
confidence: 91%